Reading Technologies From a Temporal Perspective: Evolution, Adaptation and Future Vision - Bulut, Aydın (Wiley, 2025)
ABSTRACT The present study employs a systematic thematic analysis of the extant academic literature on the subject of ‘technology in reading’ to explore its conceptual evolution and educational implications. The PRISMA framework was used to analyse 6081 peer‐reviewed articles published between 1944 and July 2025 through bibliometric methods. The findings indicate that technological innovations, including e‐books, AI‐assisted reading tools, and digital platforms, have had a growing influence on reading comprehension, motivation, and fluency, particularly in primary education and ESL contexts. Thematic analysis yielded four overarching themes: cognitive differences across mediums, pedagogical practices, early literacy tools, and critical digital reading strategies. Theoretical underpinnings were established through the utilisation of social cognitive theory, digital literacy models, and the Technology Acceptance Model (TAM), emphasising the dynamic interplay among individual, pedagogical, and contextual factors. Temporal analyses showed a pronounced increase in research activity following 2010, reaching its zenith in 2023, driven by the integration of artificial intelligence and remote learning technologies. However, the review also identified significant gaps, particularly concerning long‐term impacts, differentiated instructional practices, and critical evaluation skills in digital reading. The study provides a conceptual framework and future directions for integrating technology into reading education, emphasising the necessity for strategic, pedagogically sound implementations. The findings of this study have direct implications for the training of teachers, the development of curricula, and the formulation of educational policy.